Integrasi Konseling Berbasis Logoterapi dalam Meningkatkan Ketahanan Hidup Mahasiswa Bimbingan Konseling Islam (BKI) UIN Purwokerto dengan Keterbatasan Sumber Daya Ekonomi - Fahmi Fahrezi; Nurinawati Kurnianingsih; Amelia Nurul Aisyah; Alief Budiyono (Universitas Veteran Bangun Nusantara, 2024)
This study explores the effectiveness of logotherapy-based counseling in enhancing the resilience of students in the Islamic Guidance and Counseling (BKI) program at UIN Purwokerto, who face economic resource limitations. The research subjects were five BKI students from UIN Purwokerto, selected through purposive sampling based on specific criteria: economic resource limitations, active participation in academic activities, and openness to undergoing logotherapy-based counseling. The research method used was qualitative with a case study approach, and data were collected through in-depth face-to-face interviews, supplemented by observations and documentation. The use of face-to-face interviews allowed the researcher to gather deeper information and capture the emotional nuances and experiences of the subjects directly, which is crucial in logotherapy-based research. Data were analyzed using thematic analysis. The results showed that logotherapy-based counseling helped students find meaning in the challenges they faced, improved their emotional regulation skills, and strengthened their adaptive coping strategies. The students also reported increased self-confidence and the ability to set realistic life goals despite their limitations. These findings emphasize the important role of counselors in providing logotherapy-based support to help students overcome economic resource constraints. This study recommends the development of logotherapy-based counseling modules that can be widely applied in higher education.